1998
DOI: 10.1111/j.1528-1157.1998.tb01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Enhanced Kindliig and Hippocampal Neuronal Injury in Immature Rats with Neuronal Migration Disorders

Abstract: Summary: Purpose: Neuronal migration disorders (NMD) are often found in patients with epilepsy. However, the mechanisms linking these two pathologies are not yet fully understood. In this study, we evaluated whether NMD increased kindling seizure susceptibility and seizure-induced acute neuronal damage in the immature brain.Methods: Experimental NMD were produced by exposing pregnant rats (gestation day 15) to methylazoxymethanol acetate (MAM, 25 mgkg, ip). Seizures were induced in rat pups (postnatal day 15) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…19,20 Experimentally, hyperthermia-induced seizures themselves did not lead to spontaneous seizures in an immature rat model, 17,21 which was interpreted as evidence for febrile seizures constituting only one step in a multistage process. 17 The observation that experimentally induced migrational disorders increased the susceptibility to hyperthermia-induced seizures 22 and kindling 23 further substantiated this view. However, in the clinical setting most cases of MTLE show only the preoperative MR signs of hippocampal sclerosis.…”
mentioning
confidence: 65%
“…19,20 Experimentally, hyperthermia-induced seizures themselves did not lead to spontaneous seizures in an immature rat model, 17,21 which was interpreted as evidence for febrile seizures constituting only one step in a multistage process. 17 The observation that experimentally induced migrational disorders increased the susceptibility to hyperthermia-induced seizures 22 and kindling 23 further substantiated this view. However, in the clinical setting most cases of MTLE show only the preoperative MR signs of hippocampal sclerosis.…”
mentioning
confidence: 65%
“…This suggests that a preexisting underlying structural or functional abnormality likely facilitated the development of epilepsy. Similarly, in animal models, Germano et al (43) demonstrated that rats with neuronal migration brain lesions had a lower afterdischarge threshold, and their hippocampi would kindle more quickly than those of the control rats.…”
Section: Discussionmentioning
confidence: 93%
“…8 In addition, studies on animal models of dysplasia have shown that cortical and heterotopic subcortical structures display excessive excitability, which is manifested as a reduction in seizure threshold both in vivo and in vitro, but not with the occurrence of spontaneous seizures. [9][10][11] None of these models resemble the most clinically epileptogenic forms in humans; however, neuronal heterotopia is the most commonly reported histopathologic abnormality in resected tissue.…”
Section: Developmental Neocortical Lesionsmentioning
confidence: 95%